Democratic Rollback in West Africa: Coup Contagion, Sit-tight Tyrants and Best Options for Regional Organisations - Mike Omilusi (Lectio Socialis)

(untitled)
Unconstitutional changes of government (UCG) have resurfaced in West Africa, undermining decades of democratic progress. This article examines the effectiveness of intervention strategies by regional organizations, specifically the African Union (AU) and the Economic Community of West African States (ECOWAS), in preventing democratic backsliding and mitigating military coups. Despite these organizations’ efforts, their strategies, including diplomatic pressure, economic sanctions, and military threats, have often yielded limited success. The study investigates the strengths and weaknesses of these approaches, highlighting the inconsistency in sanctions application and the internal divisions within ECOWAS that hamper effective intervention. Through a comprehensive review of recent coups in Guinea, Burkina Faso, Niger, and Gabon, the study explores the broader political and economic factors contributing to instability, such as corruption, weak institutions, and socioeconomic challenges exacerbated by the COVID-19 pandemic. The findings suggest that enhancing democratic institutions, promoting good governance, and enforcing strict term limits are crucial for long-term stability. This study aims to contribute to the development of more robust frameworks for safeguarding democracy in West Africa, offering recommendations for regional organizations, national governments, and international actors to address the challenges of democratic backsliding and coup contagion.